PENGARUH STRUKTUR KEPEMILIKAN PUBLIK, PRAKTIK PENGELOLAAN PERUSAHAAN, JENIS INDUSTRI, UKURAN PERUSAHAAN, PROFITABILITAS DAN RISIKO KEUANGAN TERHADAP TINDAKAN PERATAAN LABA (STUDI EMPIRIS PADA INDUSTRI YANG LISTING DI BURSA EFEK JAKARTA) - Susanto, Yulius Kurnia (Journal of Indonesian Economy and Business, 2008)
This research is designed to examine the influence of companyâscharacteristics on income smoothing action among listing companies at JakartaÂ Stock Exchange. The factors being examined were public ownership structure,Â corporate governance practice, industrial type, firm size, profitability andÂ financial risk. Corporate governance practice namely audit quality, independentÂ commissioner board and audit committee.Eighty one listed companies at Jakarta Stock Exchange selected usingpurposive sampling method were used as research sample, with period from 2002Â until 2006. The sample was classified into smoother and non smoother usingÂ Eckelâs model. Data were analyzed using binary logistic regression.The results of the analysis indicated that public ownership structure,corporate governance practice, industrial type, firm size, profitability had aÂ significant influence on income smoothing action and the influence of financialÂ risk on income smoothing action was not significant.Keywords: Public ownership structure, corporate governance practice, industrialÂ type, firm size, profitability, financing risk and income smoothingÂ action.